Resilience and caregiving ability among caregivers of people with stroke: The mediating role of uncertainty in illness - Jinyao Wang; Jun Cui; Shuangyan Tu; Rong Yang; Lihong Zhao (Frontiers in Psychiatry, 2022)
BackgroundIn China, stroke survivors are usually cared for by their family members. However, the caregiving ability of these informal caregivers remain inadequate during the hospitalization of their family members following a sudden onset of a stroke, and this sudden need for care overwhelms caregivers even after the hospital discharge. Therefore, research is required to identify predictors of caregiving ability that could be targeted in future interventions aimed at improving caregiving skills and reducing the burden on caregivers who care for stroke survivors.Materials and methodsFrom August 2019 to February 2020, stroke survivors were hospitalized for the first time, and their family caregivers were registered via convenience sampling. Caregiver demographic information, resilience status, uncertainty in illness, caregiving ability, and patients' severity of stroke were measured using standardized questionnaires. Structural equation modeling was used to test the proposed model, where caregiver resilience and stroke severity predicted caregiving ability directly, and uncertainty in illness mediated the association between caregiver resilience and caregiving ability.ResultsA total of 306 dyads were included in the study. The tested model fit the data well (χ2 = 118.2, df = 64, RMSEA = 0.053, CFI = 0.946, TLI = 0.923). Statistically significant pathways linked caregivers' resilience status to uncertainty in illness (β = −0.558, S.E. = 0.022, P < 0.01), caregivers' resilience to the status of caregiving ability (β = −0.269, S.E. = 0.013, P < 0.01) and caregivers' uncertainty about the illness to caregiving ability (β = 0.687, S.E. = 0.051, P < 0.01). We also found that caregivers' uncertainty in illness mediated the association between caregivers' resilience and caregiving ability (β = −0.384, S.E. = 0.061, P < 0.01).ConclusionsOur structural equation modeling result identified resilience and uncertainty about the illness as predictors of the caregiving ability of informal family caregivers who suffered from care burdens. Supporting family caregivers to build their resilience and reduce illness uncertainty may improve caregiving for stroke survivors.